Modelling and control strategies for hydrokinetic energy harnessing - Wan Ismail, Ibrahim (2020)
The high prices and depletion of conventional energy resources and the environmental concern due to the high emission of CO2 gases have encouraged many researchers worldwide to explore a new field in renewable energy resources. The hydrokinetic energy harnessing in the river is one of the potential energies to ensure the continuity of clean, reliable, and sustainable energy for the future generation. The conventional hydropower required a special head, lots of coverage area, and some environmental issues. Conversely, the hydrokinetic system based on free stream flowing is one of the best options to provide the decentralised energy for rural and small-scale energy production. Lately, the effort of energy harnessing based on hydrokinetic technology is emerging significantly. Nevertheless, several challenges and issues need to be considered, such as turbine selection for energy conversion, generalised turbine model and control strategies for the grid and non-grid connection. To date, no detailed information on which turbines and turbine model are most suited to be implemented that match Malaysia’s river characteristics. Besides, a large oscillation has occurred on the output current and power during dynamic steady state due to the water variation and fluctuation in the river. Hence, reducing the energy extraction and controller efficiency for stand-alone and grid-connected systems, respectively. Therefore, the study aims to analyse the different turbine's design, proposed the turbine model, and propose the potential control strategies for stand-alone and grid-connected hydrokinetic energy harnessing in the river. In this work, three types of vertical axis turbines, including the H-Darrieus, Darrieus, and Gorlov with twelve different NACA and NREL hydrofoils, were analysed using the QBlade and MATLAB software, respectively. The effect of symmetrical and non-symmetrical geometry profiles, hydrofoils thicknesses, and turbine solidities have been compared to choose one of the best option turbines based on the highest power coefficient (CP) and a torque coefficient (CM), respectively. Subsequently, the turbine power model generalised equation has been proposed to represent the hydrokinetic turbine characteristic using a polynomial estimation equation. On the other hand, the MPPT control strategy is employed for the off-grid system using the sensorless method. The circuit topology based on an uncontrolled rectifier with the DC boost converter is implemented to regulate the rectifier output voltage through duty ratio. Subsequently, the metaheuristic method based on the combination of the Hill-Climbing Search (HCS) MPPT algorithm and the Fuzzy Logic Controller has been proposed to produce a variable step size compared to the fixed step size in conventional HCS algorithm. On the contrary, the dynamic model of the grid-connected hydrokinetic system has been linearised for small-signal stability analysis. The eigenvalues analysis-based approached has been applied to evaluate the system stability due to the small disturbance. The PI controller with the eigenvalues tracing method has been proposed to improve the system stability by reducing the oscillation frequency. The research outcomes indicated that the H-Darrieus with NACA 0018 was the best turbine for energy conversion in the river. Besides, the HCS-Fuzzy MPPT algorithm improved the energy extraction up to 88.30 % as well as reduced 74.47 % the oscillation compared to the SS-HCS MPPT. The stability of grid-connected hydrokinetic energy harnessing was improved up to 63.63 % by removing the oscillation frequency at states of λ8,9,10,11 as well as reducing 40.1 % oscillation of the generator stator current at the rotor side controller (RSC).